2006
DOI: 10.1007/s00114-006-0172-4
|View full text |Cite
|
Sign up to set email alerts
|

Intrageneric differences in the four stereoisomers of stenusine in the rove beetle genus, Stenus (Coleoptera, Staphylinidae)

Abstract: Most species of the rove beetle genus Stenus employ the spreading alkaloid stenusine as an escape mechanism on water surfaces. In the case of danger, they emit stenusine from their pygidial glands, and it propels them over the water very quickly. Stenusine is a chiral molecule with four stereoisomers: (2'R,3R)-, (2'S,3R)-, (2'S,3S)-, and (2'R,3S)-stenusine. The percentile ratio of these four isomers is only known for the most common species of the genus: Stenus comma. With the intention of determining the ster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…In line with our result, potential functions of the pygidial gland components of this necrophagous beetle can be attributed to pressures associated with food's characteristics, such as its degree of decomposition, contamination by fungi and bacterias (Favila and Díaz 1996;Favila 1993). Recent investigations on rove beetles have demonstrated that pygidial gland components are capable of deterring predators and protecting the beetles from infestation with microorganisms (Betz 1999;Lusebrink et al 2007;Schierling et al 2013). In this regard, the composition of pygidial secretion from Canthon c. cyanellus might have antimicrobial properties.…”
Section: Discussionsupporting
confidence: 65%
“…In line with our result, potential functions of the pygidial gland components of this necrophagous beetle can be attributed to pressures associated with food's characteristics, such as its degree of decomposition, contamination by fungi and bacterias (Favila and Díaz 1996;Favila 1993). Recent investigations on rove beetles have demonstrated that pygidial gland components are capable of deterring predators and protecting the beetles from infestation with microorganisms (Betz 1999;Lusebrink et al 2007;Schierling et al 2013). In this regard, the composition of pygidial secretion from Canthon c. cyanellus might have antimicrobial properties.…”
Section: Discussionsupporting
confidence: 65%
“…The ratio of these four stereoisomers shows intrageneric differences (Lusebrink et al 2007). The antimicrobial effect of stenusine may change with changing stereoisomer ratio, or just one enantiomer may be sufficient to inhibit the growth of microorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…The ecological significance of alkaloids in animals is probably the use as a defence against predators and microorganisms (Schlee 1985). Earlier studies have hypothesised that the pygidial gland secretion of Stenus beetles may act against microorganisms (Dettner 1993;Betz 1999;Lusebrink et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In an earlier study we showed that the ratio of the four stereoisomers of the alkaloid stenusine (4) differs with species (Lusebrink et al, 2007). The stereoisomeric ratio [(2'R,3R)-, (2'S,3R)-, (2'S,3S)-and (2'R,3S)-stenusine] of the German (GER) and Canadian (CDN) S. comma (subgenus Stenus) differs enormously: GER 17%:37%:43%:3% vs. CDN 0%:0%:55%:45%.…”
Section: Detection Structure Elucidation and Synthesis Of The Pyridmentioning
confidence: 99%